The law and regulation of international finance - Tennekoon, Ravi C. (Haywards Heath, West Sussex : Tottel Publishing, 2006)
Focuses on the major financing transactions in international financial markets - the international syndicated loan, the international bond issue, the Medium Term Note programme, the Euro-commercial paper programme and the global depository receipt issue
Cover title: The law & regulation of international finance.
Includes index.
rpm 09/09/15, ijb 28/03/2019
Loans
Keywords: Loans, Foreign --- Regulation; Bonds; Euro-bond market